2016
DOI: 10.2105/ajph.2016.303071
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Identity Disparities in Smoking and Secondhand Smoke Exposure in California: 2003–2013

Abstract: Objectives. We determined smoking prevalence, smoking behavior, and secondhand smoke (SHS) exposure of LGB-identified Californians; compared these with heterosexuals; and analyzed changes over the last decade. Methods.We analyzed the 2003-2013 California Health Interview Surveys, using multivariate logistic regression models to examine the impact of sexual identity on smoking behaviors. We conducted time trend analyses for each smoking behavior.Results. Lesbian and bisexual women smoke at higher rates than het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
4
13
0
Order By: Relevance
“…We found that the overall prevalence of current cigarette smoking was higher among sexual minorities (22.5% in LGB adults) as compared to HET adults (15.3%), which is similar to the findings of other studies (Bennett et al, 2015; Fallin et al, 2015a; Fallin et al, 2015b; Johnson et al, 2016; King et al, 2012; Lee et al, 2009; Max et al, 2016). Justifications for this high prevalence include normative behavior of socializing at bars, to cope with stress, and having friends and family who smoke (Gruskin et al, 2008; Jannat-Khah et al, 2017; Remafedi, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…We found that the overall prevalence of current cigarette smoking was higher among sexual minorities (22.5% in LGB adults) as compared to HET adults (15.3%), which is similar to the findings of other studies (Bennett et al, 2015; Fallin et al, 2015a; Fallin et al, 2015b; Johnson et al, 2016; King et al, 2012; Lee et al, 2009; Max et al, 2016). Justifications for this high prevalence include normative behavior of socializing at bars, to cope with stress, and having friends and family who smoke (Gruskin et al, 2008; Jannat-Khah et al, 2017; Remafedi, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…• There is a higher prevalence of mentholated tobacco use among LGBT smokers [9], which increases nicotine addiction levels and increases difficulty in smoking cessation [10]. • Sexual and gender minorities are more likely to be exposed to involuntary smoking than their heterosexual counterparts [11].…”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to a number of factors. For smoking, prevalence is decreasing in California as it is in the rest of the nation, though the rates for gay and bisexual men remain higher than rates for heterosexual men 6. In addition, lifestyle changes and improved treatments have resulted in fewer cases of and fewer deaths from smoking-related diseases 19.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the LGBT community, like many marginalised minorities, use tobacco at higher rates than the mainstream, which makes them more vulnerable to the harmful consequences of such behaviour 3–6. In spite of a growing movement to address tobacco addiction within the LGBT community, prevalence remains high, and tobacco use is rarely viewed as a priority issue by LGBT leaders or community members 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation